The importance of respecting accreditation indicators to improve quality of care. (30th September 2020) - Marino, A F; Centurione, E; Cofano, R; Garau, L; Ferrara, A; Pannese, C; Raimondi, A; Verlengia, L; Rivolta, S; Castelli, B
Abstract: Issue: The health and social-care facilities (HSF) of the Lombardy Region provide services specifically conceived for fragile populations, including elderly, disabled, addicts etc. Through its Accreditation Units, the Agency for Health Protection (ATS) in the Metropolitan City of Milan is responsible for overseeing authorization and accreditation indicators of HSFs in all afferent districts. Assessed requirements include the qualitative standard (presence of mandatory professional figures) and the quantitative standard (guaranteed weekly minimum time of care per patient) of operating staff, based on current legislation. Description of the problem: These standards are evaluated at site-inspection by examining staff qualifications and by matching staff working hours to actual daily presence of patients, randomly selecting a recent past week. The resulting standards may thus not be fully representative of the whole year. In 2019, the Health and Social-care facilities Accreditation Unit of ATS began a retrospective quali-quantitative analysis of health service staffing data for 2017 and 2018. Data were extrapolated from two main databases: "Scheda Struttura", a data collection tool regarding work hours, qualifications, waiting lists etc. compiled yearly by HSF managers; and economic data detailing reimbursements by the regional health service, based on effective daily presence of patients at the HSF. Results: Preliminary results relating to 2017 showed that around 4% of HSFs do not guarantee qualitative staffing standards, and almost 30% do not guarantee quantitative staffing standards throughout the year. Lessons: The proposed tool is useful for emphasizing potentially critical situations and may help define the annual inspection schedule with the aim of continuously improving quality of care among regional HSFs. Key messages: Data management tools can help local health authorities monitor and identify facilities at risk of falling below the defined standards of care. Qualitative and quantitative analysis of health service staffing is useful for emphasizing potentially critical situations and may help define the annual inspection schedule.